Letting the cat out of the bag: athletes, coaches and physiotherapists share their perspectives on injury prevention in elite sports - Bolling, C.; Barboza, S. D.; van Mechelen, W.; Pasman, H. R. (British Journal of Sports Medicine, 2020)
Objectives To explore how sports injury prevention takes place in elite sport practice and to describe the perspectives of athletes, coaches and physiotherapists regarding the most critical factors that help prevent injury in the elite sports context.